PENGARUH SENYAWA HUMAT DAN PUPUK KANDANG AYAM TERHADAP SERAPAN HARA NITROGEN DAN KUALITAS BIBIT STEK UBIJALAR (Ipomoea batatas L.) - Putri Tunjung Sari; Josi Ali Arifandi (Universitas Trilogi, 2019)
Seed cutting of sweet potato influenced by nutrient availability, especially nitrogen. Humic straw substances and cattle chicken manure fertilizer can increase the amount of nitrogen in the soil and also can improve the physical nature of soil. This study aimed to find out the influence of humic straw substances and cattle chicken manure fertilizer application toward the uptake of nitrogen nutrients for the seeds cutting quality of sweet potatoes. This research was conducted using factorial Randomized Block Design (RBD) with two factors, trere are humic straw subtances and cattle chiken manure. The variable observed was pH, C-Organic, N-Total of soil total length of plants, wet weight, dry weight, content of N-tissue, and N absorption. The result showed that a combination of humic straw substances and cattle chicken manure fertilizer influence to the increase of N-Total of soil, N-tissue, the uptake of N, the total length of plant, wet weight, and dry weight of the upper plants. The addition of a single factor of chicken manure fertilizer affects to the increase of pH and C-Organic of soil. Moreover, the best treatment combination in increasing the nitrogen uptake were A2P3 treatment (with 0.2% humic acid and 0.92 gram N of manure fertilizer). Furthermore, the best treatment combination in improving the number of seedlings cutting of sweet potatoes was A0P1 treatment (without humic acid and adding 0.46 gram N of manure fertilizer). Keywords: seed cutting of sweet potatoes, nitrogen, chiken cattle manure and humic subtances.